The Act of Fictional Communication in a Hermeneutic Pragmatic - Wood , Tahir (Research in Language, 2012)
This paper is concerned with fictional communication, as the act of an author in relation to a reader. Fictional discourse exhibits certain complexities that are not observable in other forms of discourse. For example, the author’s act is mediated for the reader by that set of persons called characters. This fact generates a range of relations, firstly the triad of author-reader, author-character, and reader-character. But closer observation reveals that this mediation may be such that it gives way to another, deeper set of relations. At the deepest level one may postulate reader’s relation to author’s self-relating and author’s relation to reader’s self-relating. These questions are explored with view to deriving a revisionist notion of pragmatics that is open to agency.